2003
DOI: 10.1016/s0301-0546(03)79170-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of a depigmented and glutaraldehyde polymerized therapeutic vaccine of Parietaria judaica

Abstract: Immunotherapy with depigmented and glutaraldehyde-polymerized extract of Parietaria judaica pollen is safe and effective to treat patients with allergic rhinitis and clinical sensitivity to this pollen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Larger studies are needed to make more definitive statements on safety. Similar favourable safety profiles were demonstrated for depigmented glutaraldehyde-polymerized allergen extracts in children and adults with allergic rhinoconjuncti-vitis and/or asthma due to HDMs and pollen [19,22,23,[36][37][38][39]. In two prospective, non-interventional studies including 175 and 766 patients who received a variety of different depigmented glutaraldehyde-polymerized allergen extracts, no grades-3 or -4 systemic reactions were reported [23,40].…”
Section: Discussionmentioning
confidence: 79%
“…Larger studies are needed to make more definitive statements on safety. Similar favourable safety profiles were demonstrated for depigmented glutaraldehyde-polymerized allergen extracts in children and adults with allergic rhinoconjuncti-vitis and/or asthma due to HDMs and pollen [19,22,23,[36][37][38][39]. In two prospective, non-interventional studies including 175 and 766 patients who received a variety of different depigmented glutaraldehyde-polymerized allergen extracts, no grades-3 or -4 systemic reactions were reported [23,40].…”
Section: Discussionmentioning
confidence: 79%
“…Although we did not compare the results in the different treatment arms with a pure placebo group, we were able to answer our original research question, which was to demonstrate the superiority of the combined treatment over SIT alone. Anyway, the superiority of these both treatment options over placebo has already been shown in previous reports [17–20, 31–33]. There are now several open‐label studies which have shown that SIT also lowers the onset of new sensitization and the progression from allergic rhinoconjunctivitis to bronchial asthma [34, 35].…”
Section: Discussionmentioning
confidence: 89%
“…Other possibilities, currently in use, include the modification of allergens with glutaraldehyde [22,23], which produces extracts with decreased IgE-binding capacity. Depigmented and polymerized allergen extracts have also been proven to be safe and clinically efficacious [6,[24][25][26][27][28][29][30], allowing for the administration of high doses in a short period of time. The safety of these vaccines has also been confirmed using a rush build-up phase in a large group of patients [31].…”
Section: Introductionmentioning
confidence: 99%